2019
DOI: 10.1111/ceo.13647
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, associations and characteristics of severe uncorrected refractive error in the Australian National Eye Health Survey

Abstract: Importance: In Australia, nationally representative data of the burden and associations of severe uncorrected refractive error are scarce. Background: To report the prevalence and characteristics of severe uncorrected refractive error in Indigenous and non-Indigenous Australians. Design: Population-based cross-sectional study. Participants: A total of 3098 non-Indigenous Australians aged 50 to 98 and 1738Indigenous Australians aged 40 to 92 living in 30 randomly selected Australian sites were examined. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“… 15 16 17 While, female patients were more susceptible to URE in some studies, 15 18 others have reported the opposite. 19 20 21 Lower education, lack of insurance, and low income have also been related to URE. 17 18 21 Type of refractive error and diabetes are among the diseases that have been associated with URE.…”
Section: Introductionmentioning
confidence: 99%
“… 15 16 17 While, female patients were more susceptible to URE in some studies, 15 18 others have reported the opposite. 19 20 21 Lower education, lack of insurance, and low income have also been related to URE. 17 18 21 Type of refractive error and diabetes are among the diseases that have been associated with URE.…”
Section: Introductionmentioning
confidence: 99%
“…Associated risk factors were older age (OR 3.59), habitation in outer regional areas (OR 1.78) and lack of an eye examination in the previous 2 years (OR 1.5) for the Indigenous group. In the non‐Indigenous group, these risk factors were older age (OR 1.51), habitation in outer regional areas (OR 0.68 for inner regional) and male gender (OR 1.30) . The comparison of risk factors alerts us to several interesting findings involving demographics, age and modifiable risk factors.…”
mentioning
confidence: 97%
“…In the current issue of the journal, Keel et al have extended their analysis to establish risk factors associated with severe uncorrected refractive error that may underpin the previously reported vision loss and blindness . In the included paper, they examined 1738 Indigenous Australians aged 40 to 92 years and 3098 non‐Indigenous Australians aged 50 to 98.…”
mentioning
confidence: 99%
See 2 more Smart Citations